Maternal and perinatal outcomes in term pregnancies with meconium-stained amniotic fluid: a cross-sectional study from a tertiary care hospital in Nepal - Bhagat, Birendra; Moktan, Himadri; Bista, Ram Bahadur; Neupane, Khim Kumari; Jaiswal, Swati; K. C., Sabina; Gupta, Sumedha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: Meconium, the gastrointestinal excreta of the fetus, was first described by Aristotle. Meconium-stained amniotic fluid (MSAF) has traditionally been considered a sign of fetal distress in presentations other than breech and is associated with adverse fetal outcomes. However, some consider fetal passage of meconium to be a physiological phenomenon that may still pose environmental hazards to the fetus before birth. This study was conducted to evaluate the maternal risk factors associated with MSAF and its effect on fetal outcome in terms of morbidity and mortality. Methods: This hospital-based cross-sectional study was conducted in the Department of Obstetrics and Gynecology, National Medical College, Birgunj, over a period of 12 months from July 2020 to July 2021. A total of 184 pregnant women fulfilling the inclusion criteria were enrolled. The cases were divided into two groups: thin meconium-stained and thick MSAF. Data analysis included various maternal and fetal parameters. Maternal risk factors and fetal outcomes were evaluated. Results: Among the 184 cases, 31.72% had thin MSAF, while 68.28% had thick meconium. The associated maternal risk factors included pregnancy-induced hypertension, anemia, oligohydramnios, intrauterine growth restriction, and prolonged labor. Cesarean section was performed in 63.03% of cases, primarily due to non-reactive cardiotocography. Of the 184 neonates, 30.43% required admission to the neonatal intensive care unit due to low Apgar scores. Perinatal death occurred in eight cases: three due to meconium aspiration syndrome (MAS), two due to sepsis, two due to birth asphyxia, and one due to pneumonitis. Conclusions: The presence of thick MSAF is associated with increased perinatal morbidity and mortality, as well as significant maternal risk factors.